Analysis of Pressure-Volume Relationship for Bulk Metallic Glasses - H. K. Rai; A. K. Misra; S. P. Shukla; A. K. Pandey (E-Journal of Chemistry)
Relationship between compression (V/V0) and pressure have been studied for five bulk metallic glasses (BMGs) viz. Zr41Ti14Cu12.5Ni10Be22.5, Zr41Ti14Cu12.5Ni9Be22.5C1, Zr48Nb8Cu12Fe8Be24, (Zr0.59Ti0.06Cu0.22Ni0.13)85.7Al14.3 and SiO2.TiO2 in the compression ranges of V/V0 =1.00 to V/V0 = 0.10. Six forms of equation of state reported in the literature have been used in the present study to calculate pressure corresponding to different values of compressions. The comparison of graph plotted between the logarithms of calculated value of pressure to logarithm of calculated value of compression (V/V0) reveals that the agreement of Brennan-Stacey equation of state (EOS) and Poirier-Tarantolla equation of state are not good. It has been found that the assumptions, on which these equations are based, do not satisfy well in case of given BMGs.